Educational, Cultural, And Participatory Strategies Of The Sabalad Community In Internalizing The Values Of Religious Moderation In Cintakarya Village - Samrotul Puadah, Pupu; Widodo, Ageng; Aedi, Ulul; Nurmahyati, Siti (Universitas Islam Negeri Raden Intan Lampung, 2026)
Religious moderation plays a vital role in promoting social harmony and preventing extremism and conflict in plural societies. This study examines the strategies used by the Sabalad Community to internalize religious moderation values and their influence on the social life of Cintakarya Village. Using a descriptive qualitative field approach, data were collected through interviews, observations, and documentation involving five informants: the community founder, one teacher and community member, two students of Bakti Karya Vocational High School, and one local resident. The findings identify three main strategies. The educational strategy integrates at-tawassut, i‘tidal, al-ishlah, and al-la‘unf into formal learning and school programs. The cultural strategy promotes tasamuh, al-muwathanah, and i‘tiraf al-‘urf through social interactions and cultural traditions. The participatory strategy develops asy-syura and al-qudwah through community involvement. Seven of the nine values were effectively internalized, while asy-syura and al-qudwah were only moderately effective due to the irregular implementation of supporting activities. Overall, these strategies encouraged students and local residents to adopt more open, balanced, inclusive, and respectful religious attitudes.